AKTIVITAS BELAJAR SISTEM DARING SISWA DI SMA NEGERI 1 BAHODOPI PADA MASA PANDEMI COVID-19 - Yulia Windarsih Windarsih; Manap Trianto; M. Abimanyu (Program Studi Tadris Ilmu Pengetahuan Alam, Fakultas Tarbiyah dan Ilmu Keguruan (FTIK), Institut Agama Islam Negeri (IAIN) Palu, 2022)
This study aims to explain the online learning activities of students at SMA Negeri 1 Bahodopi during the Covid-19 pandemic. This type of research is descriptive research. The population of this study were students of class X, XI and XII MIPA at SMA Negeri 1 Bahodopi. The sample in this study amounted to 66 students who were determined by the quota sampling technique. Data collection techniques using a questionnaire. The results of online system learning activitiesStudents during the Covid-19 pandemic were seen from 7 indicators, namely 1) visual activities obtained a percentage of 61.03%. 2) oral activities obtained a percentage of 66.8%. 3) listening activities obtained a percentage of 72.03%. 4) writing activities get a percentage of 70.15%. 5) drawing activities obtained a percentage of 76.05%. 6) mental activities obtained a percentage of 63, 03%. 7) emotional activities get a percentage of 75.06%. From this research it can be concluded that of the 7 indicators have enough categories with an average percentage of 69.16%.